A narrativa transmídia como gênero do discurso : um estudo de caso do longa-metragem Capitão América 2 o soldado invernal - Mussarelli, Felipe (Universidade Federal de São Carlos, 2017)
The current entertainment industry finds itself dominated by big media groups, whose reach starts from production through distribution until the content exhibition in many platforms, with high revenue stream. This study aimed to compare the concept of transmedia storytelling by Henry Jenkins with Mikhail Bakhtin’s language theory by means of the hypothesis of that transmedia storytelling might be a bakhtinian speech genre. For this reason, we considered Captain American: the winter soldier (Anthony Russo and Joe Russo, 2014) and its narrative expansion produced in comic, short motion videos, television series and video games. Besides analyzing the motion picture, we sought to observe in which way the three speech genre elements (theme, style and compositional content) behaved in each narrative expansion of the motion picture in comparison to the character Captain America’s narratives not linked to the motion. As a result, we noticed that, while each narrative genre element not linked to the motion behaved independently, the linked narrative elements behaved similarly leading us to the conclusion that transmedia storytelling can be considered a bakhtinian speech genre.
Transmedia storytelling as a speech genre : a case study of Captain America the winter soldier
Keywords: Transmídia; Bakhtin; Capitão América; Audiovisual; História em quadrinhos; Transmedia; Captain America; Comic books; OUTROS